Frequency of Students Fast Food Consumption, Physical Activity, and Nutritional Statustional Status at the Faculty of Health Sciences, Muhammadiyah University of Surakarta - Firmansyah; Ahsan, Erwanda Defya; Zulaekah, Siti; Puspitasari, Dyah Intan (Indonesian Journal of Human Nutrition, 2025)
Early adulthood is a transitional period from adolescence to adulthood. The cause of early adulthood experiencing excess nutrition is the availability of fast food and lack of physical activity. The aim of this study to determine the relationship between the frequency of fast food consumption and physical activity with the nutritional status of students at the Faculty of Health Sciences, Muhammadiyah University of Surakarta. This design study was observational with a cross-sectional method involving 98 students, and were selected using the Proportional Random Sampling technique. Nutritional status was obtained from Body Mass Index (BMI) calculations, frequency of fast food consumption was collected from Food Frequency Questionnaire (FFQ), and physical activity was obtained using the Physical Activity Level (PAL) questionnaire and analyzed by Rank Spearman Test. The results of the study: 33 (33.7%) respondents were overweight, 16 (16.3%) respondents were obese I and were obese II (1%). The distribution of respondents who consumed fast food in the frequent category was 85.7% and the majority did light physical activity, namely 86.7%. The results of the correlation test showed that the frequency of fast food consumption was p-value=0.000, the value of r=0.385, and physical activity was p = 0.000, the value of r=-0.240. There is a significant relationship between the frequency of fast food consumption and physical activity with the nutritional status of students at the Faculty of Health Sciences, University of Muhammadiyah Surakarta. Education needs to be given regarding nutritional status, consumption of fast food, and physical activity in the campus environment.